Effectiveness of the Online Service Management Information System (SIMPONIE) Application in Online Business Licensing Services - Gloria Erysa Meilinda Situmorang; Muhammad Ganesha Putra; Sura Fabio Mangaraja; Andi Muhammad Rafi (Journal La Multiapp, 2023)
This research discusses the effectiveness of the SIMPONIE application in improving public services in South Tangerang City according to the information system success measurement developed by William H. Delone and Ephraim R. Mclean (2016). This application is the result of a joint initiative between the Department of Investment and One Stop Integrated Services (DPMPTSP) and the Department of Communication and Information (Diskominfo) of South Tangerang City. SIMPONIE is designed with a number of features that aim to support the licensing process digitally, with the main aim of providing easy access for the public in obtaining business permits, increasing efficiency in the licensing process, and increasing the capability of government departments in serving the public. The features offered by SIMPONIE include the ability to register and apply for business permits online, tracking application status, payment of licensing fees online, notifications and communication between applicants and authorities, as well as electronic data archiving for documentation and reporting. According to research results, the SIMPONIE application has received a positive response from the people of South Tangerang City for many years. This positive reception reflects success in overcoming the challenges faced in business licensing services at the regional level. This success provides a concrete example of how information technology innovation can be used to improve efficiency, transparency and service to the community.